Operationalizing SAMR Redefinition in EFL Reading: AI as a Mediating Tool for Literacy Innovation - Duc, Doan Hoang (Digital Technologies Research and Applications, 2026)
This study examines how Artificial Intelligence (AI) can leverage the concept of Redefinition—the highest level of the Substitution-Augmentation-Modification-Redefinition (SAMR) model—to transform the teaching of English as a Foreign Language (EFL) reading from comprehension-focused activities to inquiry-driven and effective reading and writing activities. Based on socio-cultural theory, Project-Based Learning (PBL), and theoretical frameworks of digital competence, this study conceptualizes AI as a cognitive mediating framework that supports knowledge transformation rather than task automation. Using a multi-method action research design, interventions were conducted with 130 Vietnamese university students enrolled in intermediate-level English reading courses over eight weeks. Traditional reading activities were redesigned into AI-assisted projects, including multimedia infographics, podcasts, and investigative reading tasks. Quantitative data were collected through a validated 40-item questionnaire, and qualitative insights were gathered from semistructured interviews with six purposefully selected participants. The study results indicate that AI-assisted redefined reading tasks promoted higher-order thinking, synthesis, and practical application, demonstrating the successful implementation of the SAMR Redefinition methodology. Students perceive AI as a supportive learning partner, enhancing comprehension, reducing frustration, and increasing motivation and confidence. A fairly strong positive correlation (r = 0.62) was found between purposeful AI use and student engagement and reading performance. Qualitative results further suggest that AI supports continuous reading, collaborative preparation, and multimodal knowledge building, while encouraging responsible and critical use of AI. The study proposes an AI-powered SAMR framework and a pedagogical sequence of read-interpret-transform-create, providing a scalable model for teaching English as a transformative foreign language reading.